Adapting HRM Practices to Regulatory Changes: Enhancing Work Flexibility and Productivity - Saragih, Jopinus (PT. Riset Press International, 2024)
The regulatory changes introduced by the Omnibus Law (Undang-Undang Cipta Kerja) have significantly impacted Human Resource Management (HRM) practices in Indonesia, particularly in terms of work flexibility and employee productivity. This study examines the influence of these regulatory changes on work flexibility and employee productivity at ABC Company, a firm based in North Sumatra. Utilizing a quantitative approach, this research applies regression analysis within two distinct structural models. The sample comprises employees and managers of ABC Company, totaling 200 respondents. Data were collected through questionnaires and analyzed using statistical software. The results indicate a positive and significant impact of regulatory changes on work flexibility and employee productivity. These findings suggest that the Omnibus Law has initiated strategic shifts in HRM at ABC Company. Specifically, the results highlight the need for more adaptive and innovative HRM strategies to address the challenges of flexibility and productivity in a dynamic work environment. Moreover, this study provides empirical evidence of the significant impact of regulatory changes on HRM practices, particularly regarding work flexibility and employee productivity. The findings underscore the importance of adapting HRM strategies in response to regulatory changes, offering valuable insights for other companies undergoing similar transitions in workforce management. This study contributes to the broader understanding of how legislative changes can influence HRM practices and provides a foundation for future research on adaptive HRM strategies in evolving regulatory landscapes.